Effect of replacing fish meal by yeast hydrolysate on growth and intestinal function of juvenile Jian carp (Cyprinus carpio var. jian) - Yuan, Xiangyang; Liu, Wenbin; Jiang, Guangzhen; Dai, Yongjun; Desouky, Hesham Eed (Indian Journal of Fisheries, 2021)
This experiment was performed to investigate the effects of replacing fish meal in the diet of Cyprinus carpio var. jian(average weight 19.44Â±0.06 g) by yeast hydrolysate (YH), on growth, intestinal histology and function. Six hundred fishwere assigned into five groups and fed with five isonitrogenous and isocaloric diets replacing fishmeal by 0% (G1), 1%(G2), 3% (G3), 5% (G4) and 7% (G5) YH. YH supplementation at 3% level significantly increased average body weight,daily growth index, feed intake, condition factor, speciï¬c growth rate, intestinal villi length and digestive and brush-borderenzymes activity compared to the control group (p